Analisis Pengaruh Good Corporate Governance Index dan Rating Obligasi terhadap Investment Opportunity dan Struktur Modal Perusahaan (Studi pada Perusahaan Peserta CGPI Tahun 2009-2012 yang terdaftar di BEI) - Desvita Bella; Haryetti '; Ahmad Fauzan Fathoni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aimed to determine the direct and indirect effect of good corporate governance, bond rating with the investment opportunity and the capital structure on the companies participating in CGPI listed on Indonesian Stock Exchange 2009-2012. Purpose sampling method used to get our sample. Then, the analytical method used is path analysis in accordance with the purpose of research which analyzes the influence of independent variables on the dependent variable. The result shows that: (1) Good Corporate Governance Index and Bond Rating have a positive direct effect but not significant to the Investment Opportunity, (2) Corporate Governance Index has a positive direct effect but not significant to the Capital Structure, (3) Bond Rating have a negative direct effect and not significant to the capital structure, (4) Investment Opportunity have a negative indirectly effect and significant to the capital structure, (5) Good Corporate Governance Index and Bond Rating does not have an indirect effect to the Capital Structure through Investment Opportunity.Keywords : good corporate governance index, rating obligasi, investment opportunity, capital structure